(untitled) (The Review of Diabetic Studies, 2025)
Epilepsy remains one of the most prevalent neurological disorders worldwide, affecting over 50 million people and contributing significantly to premature mortality. A substantial proportion of epilepsy-related deaths are preventable, particularly those resulting from status epilepticus, seizure-related accidents, and sudden unexpected death in epilepsy (SUDEP). Paramedics, as the first point of contact in pre-hospital care, play a decisive role in mitigating these risks through timely interventions. Their responsibilities include rapid recognition of seizure activity, airway and breathing management, prevention of hypoxia and aspiration, administration of emergency medications, and safe transport to specialized care facilities. Evidence indicates that paramedic-led interventions significantly improve survival outcomes by reducing seizure duration, preventing complications, and lowering the likelihood of fatal events. Despite these advances, several barriers—such as limited epilepsy-specific training, lack of standardized protocols, and delayed emergency response times—continue to hinder optimal care delivery. This review synthesizes existing literature to explore the life-saving role of paramedics in reducing epilepsy-related mortality, identifies challenges in pre-hospital management, and proposes strategies to enhance their impact. Strengthening paramedic competencies and integrating innovative support systems can contribute to a substantial reduction in epilepsy-related deaths, ultimately improving patient safety and public health outcomes.